Integrasi Prinsip Maqashid Syariah dan ESG dalam Membangun Akuntabilitas dan Tata Kelola Investasi Syariah di Indonesia - Nurfitriana Nurfitriana; Adryan Irawan; Fitra Analia (Jurnal Riset Akuntansi Soedirman, 2026)
The growing global awareness of sustainability is driving the growth of Environmental, Social, and Governance (ESG)-based investments. Sharia investment is also emerging as an alternative that prioritizes compliance with Islamic law as well as ethical and sustainable values. However, the integration of ESG and maqashid sharia as the philosophical foundation of sharia investment has not been systematically mapped in the literature. This study aims to integrate maqashid sharia and ESG dimensions in building accountability and governance of sharia investment, as well as formulate a conceptual integration model as a reference for developing sustainable sharia investment practices. The method used is desk research with document analysis, sustainability reports of sharia issuers, and other relevant literature. The results show that the five dimensions of maqashid sharia have substantive alignment with the ESG pillars, particularly hifz al-mal in building accountability and governance, so that maqashid sharia serves as a value foundation that strengthens the legitimacy of ESG in sharia investment. The formulated integration model encompasses three levels: values ​​(maqashid as the normative basis), instruments (ESG-based sharia stock screening), and governance. Implications include strengthening regulations by the Financial Services Authority (OJK) and the Indonesian Ulema Council (DSN-MUI) and the development of an ESG-based screening index.